Key Performance Indicators for Sustainable Freight Transport and Scenario-based Impediments in Pakistan Freight Industry - Nazam Ali; Muhammad Ashraf Javid; Syed Arif Hussain; Muhammad Abdullah (Institut Teknologi Sepuluh Nopember, 2020)
Freight transport enables economic growth, market connectivity, and access to the global supply chain systems which contribute to the societal progress and inclusive development of a country. However, it may undermine the sustainable operations by incurring external costs, inefficiency, and economic losses due to non-reliability, poor services, and information systems. In this research study, the Key Performance Indicators (KPIs) for Sustainable Freight Transport Systems (SFTS) are discussed based on available literature review and standards of sustainability measurement in freight transport. Then, based on KPIs some of the scenario-based impediments are highlighted which hinder the performance of the freight transport in Pakistan for achieving sustainable development goals. The core impediments included are Strategic Determinants (SD), Information Systems (IS), Infrastructure Management Systems (IMS) and City Logistics (CL). The negative direct impacts of the key identified factors are also highlighted and linked with each scenario-based impediment. This research study would provide an opportunity for the stakeholders to get tangible idea for policy making and upgradation of the freight transport industry in the country. The highlighted implications will also be validated via expert surveys and Delphi-analysis in the future study.